Continuous biohydrogen production by thermophilic dark fermentation of cheese whey: Use of buffalo manure as buffering agent. (23rd February 2017) - Ghimire, Anish; Luongo, Vincenzo; Frunzo, Luigi; Pirozzi, Francesco; Lens, Piet N.L.; Esposito, Giovanni
Abstract: Biohydrogen (H2 ) production from dark fermentation processes is inhibited at low culture pH (<4.0). This work investigated the culture pH and H2 production stability during the dark fermentation of cheese whey, supplemented with buffalo manure. The co-fermentation of cheese whey, rich in high carbohydrate but yielding acidic pH, with buffalo manure characterized by a high alkalinity, is promising for continuous H2 production in dark fermentation. At a cheese whey to buffalo manure ratio of 4 g VS/g VS, a maximum H2 yield and production rate of respectively, 152.2 (±43.9) mL H2 /g VS and 215.4 (±62.1) mL H2 /L/d, were achieved at an organic loading rate of 2.1 g VS/L/d of cheese whey at a stable culture pH of 4.8–5.0. The use of buffalo manure improved the H2 production stability and could replace chemical buffering agents of scaled-up dark fermentation applications. Highlights: Thermophilic dark fermentative conversion of cheese whey to H2 is presented. Addition of buffalo manure stabilizes culture pH at 4.8–5.0. Co-fermentation of cheese whey with buffalo manure enhanced H2 production stability. Buffalo manure can replace chemical buffering agents of scaled-up DF.